2014
DOI: 10.1177/0269215514527595
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of eccentric vs. concentric graded exercise in chronic tennis elbow (lateral elbow tendinopathy)

Abstract: Eccentric graded exercise reduced pain and increased muscle strength in chronic tennis elbow more effectively than concentric graded exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 33 publications
0
82
0
13
Order By: Relevance
“…“Figure 2. Photograph showing exercise set-up with the patient seated in an armchair with forearm support, holding the dumbbell (a plastic container with a specified amount of water) in the affected arm, and performing exercise by lifting and lowering the container by extension or flexion of the wrist”24…”
Section: Resultsmentioning
confidence: 99%
“…“Figure 2. Photograph showing exercise set-up with the patient seated in an armchair with forearm support, holding the dumbbell (a plastic container with a specified amount of water) in the affected arm, and performing exercise by lifting and lowering the container by extension or flexion of the wrist”24…”
Section: Resultsmentioning
confidence: 99%
“…Systematic review [15] and RCT [28] favor eccentric over other types of contractions in the management of LET, but Martinez -Silvestrini et al, [29] stated that, unlike Achilles tendinopathy, LET is often related to forceful grip activities requiring isometric contraction, which would be more beneficial than eccentric contraction in LET. LET is often related to forceful grip activities requiring isometric contraction of the wrist flexors and extensors [30].…”
Section: Discussionmentioning
confidence: 99%
“…38 -42 Two studies reported differences in baseline characteristics; however, these differences were controlled for in the analyses. 40,41 Two of the 5 studies did not adequately describe whether there were cointerventions 39,41 The study with a high risk of bias had important methodological limitations. Specifically, there were important differences in baseline characteristics between treatment groups that were not adjusted for in the analysis.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…Two trials reported that no adverse events were associated with performing the investigated strengthening or stretching exercises. 41,42 The other 3 studies did not report on adverse events. 38 -40 …”
Section: Summary Of Evidencementioning
confidence: 99%